Balancing the autonomic nervous system to reduce inflammation in rheumatoid arthritis. (26th May 2017) - Koopman, F. A.; van Maanen, M. A.; Vervoordeldonk, M. J.; Tak, P. P.
Abstract: Imbalance in the autonomic nervous system (ANS) has been observed in many established chronic autoimmune diseases, including rheumatoid arthritis (RA), which is a prototypic immune‐mediated inflammatory disease (IMID). We recently discovered that autonomic dysfunction precedes and predicts arthritis development in subjects at risk of developing seropositive RA. In addition, RA patients with relatively high vagus nerve tone (higher parasympathetic parameters, measured by heart rate variability) respond better to antirheumatic therapies. Together, these data suggest that the ANS may control inflammation in humans. This notion is supported by experimental studies in animal models of RA. We have found that stimulation of the so‐called cholinergic anti‐inflammatory pathway by efferent electrical vagus nerve stimulation (VNS) or pharmacological activation of the alpha7 subunit of nicotinic acetylcholine receptors (α7nAChR) improves clinical signs and symptoms of arthritis, reduces cytokine production and protects against progressive joint destruction. Conversely, increased arthritis activity was observed in alpha7nAChR knockout mice. These studies together with previous work in animal models of sepsis and other forms of inflammation provided the rationale for an experimental clinical trial in patients with RA. We could for the first time show that an implantable vagus nerve stimulator inhibits peripheral blood cytokine production in humans. VNS significantly inhibited TNF and IL‐6 production and improved RA disease severity, even in some patients with therapy‐resistant disease. This work strongly supports further studies using a bioelectronic approach to treat RA and other IMIDs. Abstract : Content List – Read more articles from the symposium: 13th Key Symposium – Bioelectronic Medicine: Technology Targeting Molecular Mechanisms.